2017
DOI: 10.1148/radiol.2017161683
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Neoadjuvant Chemotherapy for Breast Cancer by Using Three-dimensional Subharmonic Aided Pressure Estimation and Imaging with US Contrast Agents: Preliminary Experience

Abstract: Purpose To determine whether three-dimensional subharmonic aided pressure estimation (SHAPE) and subharmonic imaging can help predict the response of breast cancer to neoadjuvant chemotherapy. Materials and Methods In this HIPAA-compliant prospective study, 17 women (age range, 45-70 years) scheduled to undergo neoadjuvant therapy for breast cancer underwent ultrasonography (US) immediately before therapy and at completion of 10%, 60%, and 100% of chemotherapy. All patients provided written informed consent. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…A more recent experiment in rats with breast cancer xenografts also demonstrated a linear relationship between TIP and SHAPE measurements (r ¼ 0:69; p < 0:01) (Halldorsdottir et al, 2017). Albeit based on a small sample size, it has been concluded that SHAPE has potential to help predict response to neoadjuvant chemotherapy for breast cancer as early as completion of one cycle of therapy (Nam et al, 2017). Despite these encouraging results, the average error associated with these in vivo US-based SHAPE measurements has been reported to exceed 6 mm Hg (Halldorsdottir et al, 2017) so improvements in pressure estimation technology and accuracy may be needed if this treatment indicator is to be adopted in clinical practice.…”
Section: Figmentioning
confidence: 99%
“…A more recent experiment in rats with breast cancer xenografts also demonstrated a linear relationship between TIP and SHAPE measurements (r ¼ 0:69; p < 0:01) (Halldorsdottir et al, 2017). Albeit based on a small sample size, it has been concluded that SHAPE has potential to help predict response to neoadjuvant chemotherapy for breast cancer as early as completion of one cycle of therapy (Nam et al, 2017). Despite these encouraging results, the average error associated with these in vivo US-based SHAPE measurements has been reported to exceed 6 mm Hg (Halldorsdottir et al, 2017) so improvements in pressure estimation technology and accuracy may be needed if this treatment indicator is to be adopted in clinical practice.…”
Section: Figmentioning
confidence: 99%
“…To date, there are numerous reports about microbubbles as sensors for the local blood pressure measurements through detecting disappearance time of free bubbles [5,6], shift of the first harmonic or subharmonic resonance frequency [4,7,8,9,10,11,12], or amplitude variation of the scattered echo of microbubbles [1,3,10,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. Among them, amplitude variation of the scattered echo is most attractable and promising for clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to SonoVue, other microbubble ultrasound contrast agents, such as Sonazoid and Definity, have been investigated as potential pressure sensors. These have shown potential as noninvasive pressure sensors in the right ventricle [5], for diagnosing portal hypertension [39], and for estimating tumor interstitial fluid pressure in breast cancer [40]. One disadvantage of using SonoVue, compared with Sonazoid or Definity, is its nonunique subharmonic amplitudes from 0-to 200-mmHg hydrostatic pressures.…”
Section: E Clinical Implicationsmentioning
confidence: 99%